The Kazakhstan medicinal flora survey in a leading families volume - Grudzinskaya, L.M.; Gemejiyeva, N.G.; Karzhaubekova, Zh.Zh. (Fundamental and Experimental Biology, 2020)
It has been perfomed a comprehensive survey of botany — pharmacological research of 7 leading families of medicinal flora in Kazakhstan which combine 648 species (46 per cent of all pharmaceutical flora). The leading families encompassing the largest number of species are Asteraceae (196 species),Rosaceae (89), Lamiaceae и Fabaceae (78), Ranunculaceae (75), Apiaceae (69), Brassicaceae (63). The families to be analyzed include 109 pharmacopoeia species (some 47 per cent of all known species in Kazakhstan of official medicine) and 18 rare ones. Research on resource potential of medicinal species within analysed families has been extremely low. Out of 648 medical herbs raw materials inventory has been defined only for 88 that makes up some 3.6 % species of plants of 7 leading families, among them there are 50 species to be applied to official medicine. The introduction research of medicinal plants is substantially high than recource one. In the territory of Kazakhstan has been tested in crop about 40 per cent of the plants of families mentioned above. The features of farming techniques have been worked out only for 15 pharmacopeia species; the crop yields of medicinal plants in crop have been defined for 70 species of leading families.